Flood routing and alluvial aquifer recharge along the ephemeral arid Kuiseb River, Namibia - Morin, Efrat; Grodek, Tamir; Dahan, Ofer; Benito, Gerardo; Kulls, Christoph; Jacoby, Yael; Langenhove, Guido Van; Seely, Mary; Enzel, Yehouda (Journal of hydrology (Amsterdam), 2009)
Flood water infiltrates ephemeral channels, recharging local and regional aquifers, and it is the main water source in hyperarid regions. Quantitative estimations of these resources are limited by the scarcity of data from such regions. The floods of the Kuiseb River in the Namib Desert have been monitored for 46 years, providing a unique data set of flow hydrographs from one of the world’s hyperarid regions. The study objectives were to: (1) subject the records to quality control; (2) model flood routing and transmission losses; and (3) study the relationships between flood characteristics, river characteristics and recharge into the aquifers. After rigorous quality-testing of the original gauge-station data, a flood-routing model based on kinematic flow with components accounting for channel-bed infiltration was constructed and applied to the data. A simplified module added to this routing model estimates aquifer recharge from the infiltrating flood water. Most of the model parameters were obtained from field surveys and GIS analyses. Two of the model parameters—Manning’s roughness coefficient and the constant infiltration rate—were calibrated based on the high-quality measured flow data set, providing values of 0.025 and 8.5 mm/h, respectively. This infiltration rate is in agreement with that estimated from extensive direct TDR-based moisture measurements in the vadose zone under the Kuiseb River channel, and is low relative to those reported for other sites. The model was later verified with additional flood data and observed groundwater levels in boreholes. Sensitivity analysis showed the important role of large and medium floods in aquifer recharge. To generalize from the studied river to other streams with diverse conditions, we demonstrate that with increasing in infiltration rate, channel length or active channel width, the relative contribution of high-magnitude floods to recharge also increases, whereas medium and small floods contribute less, often not reaching the downstream parts of the arid ephemeral river at all. For example, more than three-quarters of the floods reaching the downstream Kuiseb River (with an infiltration rate of 8.5 mm/h) would not have reached similar distances in rivers with all other properties similar but with infiltration rates of 50 mm/h. The recharge volume in the downstream segment in the case of higher infiltration is mainly contributed by floods with magnitude ⩾93rd percentile, compared to floods in the 63rd percentile at an infiltration rate of 8.5 mm/h.